Modelling the Cost of the Wind: A Preliminary Reassessment of Networks of Mobility in the Late Bronze Age Mediterranean - Paula Gheorghiade; Christine Spencer (Journal of Computer Applications in Archaeology, 2024)
Although maritime seascapes afford potentials for connectivity and mobility, they are also greatly impacted by seasonality and available sailing technology. These crucial environmental and technological parameters are often considered in the reconstruction of potential maritime routes, especially for long-distance open water voyaging, but their formal incorporation into quantitative models of maritime mobility remains limited. The present paper considers seasonality, distance, temporality, and sailing technology in exploring potentials for mobility from Crete across the larger east Mediterranean during the LBA. Using GIS functionality, we create a cost-surface model that incorporates seasonal winds with archaeological and technological variables to create a more dynamic and representative seascape illustrated by modeling mobility from the site of Kommos, Crete. We also demonstrate how null models that rely only on Euclidean distance as a parameter for mobility across land and sea can be improved with more dynamic, cost-surface maritime models.